Dampak Pendapatan Asli Daerah (PAD) Dan Indeks Pembangunan Manusia (IPM) Terhadap Angka Kemiskinan Di Kabupaten Pandeglang - Banten - Desmintari Desmintari; Lina Aryani (Universitas Mercu Buana, 2019)
Pandeglang City is a buffer for the Special Capital Region of Jakarta, where most of the population of Pandeglang Regency works in Jakarta and settlements in Pandeglang Regency, who go to Jakarta every day to work and mostly live on fishing / fishing and farming in terms of welfare. so poverty in Pandeglang Regency is still relatively high. Regional Original Income, the Human Development Index also affects the life of the community in Pandeglang district classified as prosperous or not. This research was conducted in order to analyze the Regional Revenue and Human Development Index of poverty in the Pandeglang Regency in 2010-2017 with the aim of analyzing the influence of regional income and human development indices on the number of poor people in Pandeglang Regency by analyzing how much progress and increase development in Pandeglang district has always been influenced by its citizens and local original income. By using the analytical tool used is the OLS analysis with the results of Local Revenue significantly influence Poverty Rate. And the independent variable Human Development Index Value significantly influence the Poverty Rate